A Cooperative Learning Intervention to Promote Social Inclusion in Heterogeneous Classrooms - Klang, Nina; Olsson, Ingrid; Wilder, Jenny; Lindqvist, Gunilla; Fohlin, Niclas; Nilholm, Claes (Frontiers in Psychology, 2020)
Concerning challenges with the social inclusion of children with special educational needs (SEN), it is imperative to evaluate teacher interventions that promote social inclusion. This study aimed to investigate the effects of cooperative learning (CL) intervention on social inclusion. In addition, it was investigated to what degree CL implementation affected the outcomes. Fifty-six teachers of 958 fifth-grade children were randomly selected to intervention and control groups upon recruitment to the study. The intervention teachers received training and coaching in CL and implemented this approach three to four times a week for 15 weeks. The results showed a significant but small effect of CL on children’s social acceptance, but no significant effect on children’s friendships and perceptions of classroom relationships. The degree of CL implementation had effect on children’s social acceptance, but the effect was not consistent across social acceptance measures as a friend or a groupmate. Thus, it can be concluded that CL, conducted with the length and intensity of this study, may not lead to substantial changes in the social inclusion of children with SEN. In future studies, more focus needs to be devoted to teacher implementation of the CL approach.